Importance of temperature for the willow bodyguard Perilitus brevicollis - Baffoe, Kwabena (2011)
The influence of temperature on the performance of the willow bodyguard, Perilitus brevicollis Haliday, 1835 (Hymenoptera: Braconidae) as well as the impact of temperature and parasitism on its host feeding capacity were assessed. The study also aimed at identifying the similarities and differences among two populations (Swedish and Irish) with regards to parasitoid diversity, size and parasitism rate. To achieve the former objective of the study, P. brevicollis parasitized adult Phratora vulgatissima were reared under four constant temperatures (10, 15, 20, 25 ℃) in the laboratory. It was then revealed that: (i) development rate was faster at the higher temperatures and vice versa; (ii) larger adult parasitoid size were achieved at the lower temperature (10 ℃) and smaller at the highest temperatures (25 ℃); (iii) 20 ℃ was found to be an optimal temperature for survival; (iv) host feeding capacity was reduced by the combine effect of parasitism and temperature especially at the higher temperatures. To achieve the second objective, overwintering adult beetles were collected from two sites in Sweden and Ireland and were reared in the greenhouse. The result indicated that, P. brevicollis was common to the two countries with no other species identified. These results from the two experiments underlie the importance of temperature in rearing the parasitoid for biological control program as well as predicting the performance of the parasitoid in future climates. The result also serves as basis for choosing parasitoid to control Phratora beetles in different geographical areas.